Rofecoxib-Induced Hepatotoxicity: A Forgotten Complication of the Coxibs - Brian Yan; Yvette Leung; Stefan J Urbanski; Robert P Myers (Canadian Journal of Gastroenterology)
Rofecoxib is a member of the coxib family of nonsteroidal anti-inflammatory drugs that selectively inhibit cyclooxygenase-2. Although the coxibs are generally well-tolerated, rofecoxib was recently withdrawn from the market due to concerns regarding cardiovascular safety. Rare cases of hepatic injury attributable to the coxibs have been reported. In the present study, two additional cases of severe hepatotoxicity are described in patients with cholestatic symptoms and abnormal liver biochemistry, shortly following the initiation of rofecoxib for arthritic complaints. In both cases, liver histology was compatible with drug-induced hepatotoxicity, and rapid clinical and biochemical improvements were observed following rofecoxib discontinuation. With new coxibs and expanding indications on the horizon, physicians in all areas of practice must be aware of this disorder and consider it in any patient who develops hepatic dysfunction after taking a coxib.